Do the Quality of Investigation Audit Influenced by Auditor Independ-ence and Professionalism? - Mahendro Sumardjo; Dewi Darmastuti; Najmatuzzahrah Najmatuzzahrah (International Business and Accounting Research Journal, 2022)
This study examined the influence of independence and professionalism on the quality of investigation audit. This is a survey study conducted in the Law Enforcement Agencies in Indonesia, consisting of the Indonesian National Police, the Attorney General's Office, and the Corruption Eradication Commission. The unit of analysis is their investigators as respondents. The research instrument was built base on the operationalization of variables developed by previous research. Furthermore, the data were analyzed using descriptive statistical analysis and structural equation modelling (SEM) techniques. The results of this study provide empirical evidence that independence and professionalism have a significant positive effect on the quality of investigation audit. The model in this study can be used to measure the quality of investigation audit from the perspective of independence and professionalism.